Scott, Foresman beginning dictionary - Thorndike, Edward L. (Edward Lee) 1874-1949.; Barnhart, Clarence Lewis 1900-. (Glenview, Ill. Scott, Foresman, 1976)
A beginning dictionary including illustrations and examples of usage in the definitions and exercises and lessons teaching use of a dictionary.
First published in 1945 under title: Thorndike Century beginning dictionary; 1952-1974 ed. published under title: Thorndike-Barnhart beginning dictionary.
Keywords: English language -- Dictionaries, Juvenile; English language -- Dictionaries